Aboriginal world views and colonisation: implications for coastal sustainability†. Issue 7 (2nd July 2016) - Stocker, Laura; Collard, Leonard; Rooney, Angela
Abstract : In this paper, we show how the Aboriginal people in the south-west of Australia (the Nyungar) developed systems of knowledge, of caring for country and of family relations that enabled them to survive for tens of thousands of years and continue to have importance today. The impacts of British colonisation on cultural continuity and knowledge in the south-west have been significant and include loss of land, break-up of families and massacre. These practices led to a loss of knowledge of language and culture in some cases. However, Nyungar culture is alive and dynamic, constantly being reclaimed, re-energised and rebuilt through the interaction of contemporary and traditional research praxis. Focusing on Derbal Nara (Cockburn Sound) on the coast in the southern metropolitan area of Perth, we provide case examples of the action-research-learning methodologies used by Whadjuk Nyungar Traditional Owners. We also provide examples of stories about Derbal Nara that are still alive and being recounted up to the present day, including those that account for the recent ice age and the end of the ice age 8000 years BC when sea levels rose, drowning land in the area of Derbal Nara. Finally, we argue that Whadjuk Nyungar experiences and world views based on relationality and reflexivity are central to sustainable coastal management and that in some respects there has already been a convergence of Indigenous and Western coastal management. We present a set of principles that support the development of this "third space" for coastal sustainability.